Negative Effects of Acrolein on the Body (Texas Journal of Agriculture and Biological Sciences, 2022)
Acrolein is a clear or yellow liquid that burns quickly and breaks down quickly. This substance has a strong unpleasant odor and is mainly used in the synthesis of acrylic acid. The process of its formation (vegetable oil) is the combustion of various air pollutants, such as tobacco smoke, some fuels, gasoline, oil. Acrolein can be absorbed by the body by consuming a variety of fried foods. If a person breathes air containing acroelin, it enters these cells in a matter of seconds. Swallowing it or pushing it on the skin also causes it to be quickly absorbed into the body. Acrolein causes oxygen deficiency in the cell. The use of antioxidant phytopreparations against its damage is very effective